2023
DOI: 10.1186/s12884-023-05491-y
|View full text |Cite
|
Sign up to set email alerts
|

Additional single dose GnRH agonist during luteal phase support may improve live birth rate in GnRHa-HRT frozen–thawed embryo transfer cycle: a retrospective cohort study

Abstract: Background GnRH agonist (GnRHa) has been reported to have direct effects and functional roles in the endometrium and embryos. Several meta-analyses have shown that GnRHa administration in the luteal phase improved the live birth rate or pregnancy rate in both fresh and frozen embryo transfer (FET) cycles. The aim of this study was to investigate whether luteal GnRHa administration could also improve in vitro fertilization (IVF) outcomes in patients undergoing hormone replacement therapy (HRT) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Adding one luteal dose of GnRHa may increase the live birth rate in individuals receiving the GnRHa-HRT protocol, according to a recent retrospective cohort research. The multivariate analysis revealed that luteal GnRHa administration was positively associated with ongoing pregnancy (OR 2.04, 95% CI 1.20-3.47, P = 0.008) and live birth (OR 2.03, 95% CI 1.20-3.45, P = 0.009) (33). In line with the study of Seikkula, our data showed a distinct but statistically insignificant difference in miscarriage (10.3% vs 25%) and LBR (40.7% vs 28.6%) between the patients with or without GnRH-a based on the standard luteal support.…”
Section: Discussionmentioning
confidence: 99%
“…Adding one luteal dose of GnRHa may increase the live birth rate in individuals receiving the GnRHa-HRT protocol, according to a recent retrospective cohort research. The multivariate analysis revealed that luteal GnRHa administration was positively associated with ongoing pregnancy (OR 2.04, 95% CI 1.20-3.47, P = 0.008) and live birth (OR 2.03, 95% CI 1.20-3.45, P = 0.009) (33). In line with the study of Seikkula, our data showed a distinct but statistically insignificant difference in miscarriage (10.3% vs 25%) and LBR (40.7% vs 28.6%) between the patients with or without GnRH-a based on the standard luteal support.…”
Section: Discussionmentioning
confidence: 99%